(untitled) (Fiep Bulletin - online, 2015)
The present study aims to analyze the influence of a two-month walking program oriented on blood pressure (BP) in hypertensive individuals. 05 adults of both sexes with an average age of 55.2 ± 15.49 years, being selected for deriving intentional extension project "Walking for Health" were observed. The blood pressure measurement was taken for 02 months. The collected data was performed before the intervention of the walking program and after their action. The investigated sample exhibited significant reductions (- 12, 77 and 4, 93 mmHg for systolic and diastolic blood pressure, respectively). We conclude that the program of guided walking exerted a positive effect on blood pressure in hypertensives.